Implementasi Good Corporate Governance Pada PT Vale Indonesia Tbk Tahun 2024 : Studi Kasus Kualitatif Pada Tantangan Regulasi Multi – Level dan Integrasi ESG - Vema Fanaya Putri; Venni Avionita (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at PT Vale Indonesia Tbk in 2024 and identify the barriers faced in its implementation. A qualitative approach with a case study design was used, analyzing data from corporate documents, sustainability reports, and related regulations. The results show that PT Vale has comprehensively implemented the principles of transparency, accountability, responsibility, independence, and fairness, as reflected in the high ACGS score. However, the implementation of GCG still faces obstacles related to multi-level regulatory complexities, supply chain compliance, and post-divestment coordination challenges. This study recommends the implementation of an integrated G-GRC system, enhancing ESG-based leadership capacity, and updating the whistleblowing mechanism to address these barriers.